Modern food microbiology - Aneja, K. R. (Medtech, 2018)
Food Microbiology, an applied branch of microbiology, is an alive science directly related to human health and longevity having ample job opportunities for food microbiologists. It can be defined as the study of microorganisms and food in relation to food contamination, food spoilage, food poisoning, food preservation, food bio processing and food legislation. Modern Food Microbiology is a clearly written textbook with the student in mind belonging to food science, microbiology, biotechnology, public health, nutrition, and dietetics, and veterinary science. The summary and multiple choice questions at the end of each chapter are very useful for a quick revision and recapitulation by the students.